Przemoc seksualna wobec osób z niepełnosprawnością intelektualną - Karwacka, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The article discusses the problem of sexual violence towards people with intellectual disabilities. It presents the definition and occurrence of this phenomenon by taking into account the difficulties in estimating the scale of sexual violence towards people with intellectual disabilities. Risk factors for sexual violence that are typical of the general population and people with intellectual disability are analyzed. People with intellectual disabilities are characterized as victims of sexual abuse. This article also deals with the consequences of experiencing sexual violence for the development of people with intellectual disabilities.